Writing Apprehension in the Writing Class: Indonesian EFL Learners Context - Hanna Sundari; Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
The aims of Writing Apprehension in the Writing Class: Indonesian EFL Learners Context research is to find out the correlation between writing apprehension towards students’ writing skill. The research was located in Universitas Indraprasta PGRI Jakarta. This research was held from August 2015 to January 2016. The method of this research was quantitative approach using survey method. The analysis of the data used Pearson Product Moment Correlation. The population was the students of Unindra who took writing subject that consist of three classes; meanwhile the number of samples was 66 students who were chosen randomly. And the instruments are questionnaire by Cheng (2004) namely The Second Language Writing Anxiety Inventory (SLWAI) and English writing test. The data was analyzed quantitatively by using SPSS 17.0. The research result showed that writing performance was seemingly good with 72 average score; meanwhile, writing apprehension scored 69.98 which indicate that the students apparently do not feel very anxious during writing the paper. Moreover, the t score (-1.22) and the significant score (0.0311) were very on top of the sig. score (0.05). It can be said that H0 is accepted and Ha is rejected. We can draw a conclusion that there is no significant correlation between writing apprehension and writing performance for academic writing in higher education level.